The Contribution of Artificial Intelligence to Enhancing Operational Efficiency and Innovation in Iraqi Production Companies - An Analytical Study - Athraa Saad Hassan (Peerian Journals Publishing, 2025)
The application of artificial intelligence presents opportunities and challenges for human resources in the sales and marketing department. This study aims to analyze how human resources at the General Company for Automotive Industries in Iraq are dealing with digital transformation in the era of artificial intelligence. The research adopts a qualitative descriptive approach, relying on indepth interviews, observations, and documents. This research contributes to current practices and academic studies on the application of artificial intelligence, highlighting how industrial companies coordinate AI resources and capabilities to drive the digital transformation of the organization, while creating a competitive advantage. The data collected is analyzed using the interactive model approach by (Miles and Huberman .1994), which involves three main stages: data reduction, data display, and conclusion drawing and verification. The findings indicate that AI enhances operational efficiency and service personalization but faces challenges such as employee resistance and a digital skills gap. Continuous training strategies and adaptive AI integration are essential for the successful implementation of this technology
Keywords: Artificial Intelligence; Transformation Strategies; General Automotive Manufacturer